2000
DOI: 10.1073/pnas.090034797
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel Na v 1.6 is localized at nodes of Ranvier, dendrites, and synapses

Abstract: Voltage-gated sodium channels perform critical roles for electrical signaling in the nervous system by generating action potentials in axons and in dendrites. At least 10 genes encode sodium channels in mammals, but specific physiological roles that distinguish each of these isoforms are not known. One possibility is that each isoform is expressed in a restricted set of cell types or is targeted to a specific domain of a neuron or muscle cell. Using affinitypurified isoform-specific antibodies, we find that Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
452
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(483 citation statements)
references
References 38 publications
21
452
0
1
Order By: Relevance
“…1A3). These results indicate that Na V 1.1 and Na V 1.6 are the predominant sodium channels in the cell bodies and dendrites of Purkinje neurons, in agreement with previous work (Westenbroek et al, 1989;Gong et al, 1999;Caldwell et al, 2000;Jenkins and Bennett, 2001;Schaller and Caldwell, 2003). The observed distribution of Na V channels in P13-P14 cerebellar neurons in our experiments indicates that Na V 1.1 and Na V 1.6 channels conduct nearly all sodium current in Purkinje neurons in this age range.…”
Section: Resultssupporting
confidence: 93%
“…1A3). These results indicate that Na V 1.1 and Na V 1.6 are the predominant sodium channels in the cell bodies and dendrites of Purkinje neurons, in agreement with previous work (Westenbroek et al, 1989;Gong et al, 1999;Caldwell et al, 2000;Jenkins and Bennett, 2001;Schaller and Caldwell, 2003). The observed distribution of Na V channels in P13-P14 cerebellar neurons in our experiments indicates that Na V 1.1 and Na V 1.6 channels conduct nearly all sodium current in Purkinje neurons in this age range.…”
Section: Resultssupporting
confidence: 93%
“…The kinetically fast and tetrodoxin-sensitive Na v 1.6 sodium channel is the dominant sodium channel at mature nodes (Caldwell et al, 2000). The newly constructed nodes of Ranvier on regenerated axons positioned between GFP internodes expressed Na v 1.6, but not Na v 1.2.…”
Section: Discussionmentioning
confidence: 94%
“…Immunocytochemical studies showed a high level of Nav1.2 immunoreactivity in the mossy fiber tract [83]. Furthermore, Nav1.2 and Nav1.6 immunoreactivity are often colocalized in nonmyelinated axons throughout the entire brain [18]. This suggests that native presynaptic channels in mossy fiber Fig.…”
Section: Abstract Presynaptic Recording Mossy Fiber Boutons Mossymentioning
confidence: 96%